Spatiotemporal Variation and Networks in the Mycobiome of the Wheat Canopy - Sapkota, Rumakanta; Jørgensen, Lise N.; Nicolaisen, Mogens (Frontiers in Plant Science, 2017)
The phyllosphere is an important habitat for a diverse microbiome and an important entry point for many pathogens. Factors that shape the phyllosphere microbiome and also the co-existence among members and how they affect disease development are largely understudied. In this study we examined the wheat mycobiome by using metabarcoding of the fungal ITS1 region. Leaf samples were taken from four cultivars grown at two locations in Denmark. Samples were taken from the three uppermost leaves and at three growth stages to better understand spatiotemporal variation of the mycobiome. Analysis of read abundances showed that geographical location had a major effect in shaping the mycobiome in the total dataset, but also leaf position, growth stage and cultivar were important drivers of fungal communities. Cultivar was most important in explaining variation in older leaves whereas location better explained the variation in younger leaves, suggesting that communities are shaped over time by the leaf environment. Network analysis revealed negative co-existence between Zymoseptoria tritici and the yeasts Sporobolomyces, Dioszegia and Cystofilobasidiaceae. The relative abundance of Z. tritici and the yeasts was relatively constant between individual samples, suggesting that fast growing fungi rapidly occupy empty space in the phyllosphere.